People Living With Epilepsy Exploring socio cultural determinants affecting their life - Rani, Ajita; Talwar, Upmesh K.; Singh, Ravinder; Gautam, V K S (International Journal of Health, 2014)
Socio-cultural determinants affecting People Living with Epilepsy (PLWE) were explored between August 2010 and November, 2011 in Bareilly district of North India. Results reveal various aspects of their life: onset of first seizure, duration of suffering, their perception about daily life, marriage, family burden, etc. Further, it explored their activities during before and after treatment? PLWE face Stigma in the family as well as in their community. The capacity to do work and earn and expenditure incurred on hospital visits were major determinants affecting their life. Relationship of PLWE with other people and involvement in Community are other crucial socio-cultural determinants affecting their life. Keywords: Epilepsy, PLWE, Seizure, Stigma.